The Use of Trendelenburg Position in the Management of Retropharyngeal Abscess: A Case Report and Clinical Considerations - Emilia Nissa Khairani; Liliriawati Ananta Kahar; Novialdi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Retropharyngeal abscess (RPA) is a serious deep neck space infection that can lead to life-threatening complications such as airway obstruction, mediastinitis, and sepsis. The Trendelenburg position, where the patient's head is lower than their feet, has been traditionally used in the management of RPA to prevent aspiration of pus in case of abscess rupture. However, the optimal positioning for patients with RPA remains a topic of debate. Case presentation: A 51-year-old male patient presented to the emergency room with a 5-day history of progressive dysphagia and neck swelling. He was diagnosed with a ruptured retropharyngeal abscess extending to the mediastinum (descending necrotizing mediastinitis). The patient underwent surgical drainage and was subsequently admitted to the intensive care unit (ICU), where he was intubated and mechanically ventilated in the Trendelenburg position. Five days later, the patient developed pneumonia, suspected to be ventilator-associated pneumonia (VAP). Conclusion: The Trendelenburg position may be considered in the management of RPA to minimize the risk of aspiration. However, it is essential to weigh the potential benefits against the risks, including VAP, and to consider alternative positions such as the lateral Trendelenburg position, which may offer similar benefits with reduced risk. Further research is needed to determine the optimal positioning strategy for patients with RPA.